An industrial quality control study on Italit Construction and Development Corporation - De Celis, Excel Ann C. (College of Engineering, 2001)
Italit Construction and Development Corporation is a Filipino Corporation which has been manufacturing construction materials since 1960. By 1985, they became the only total pipe company in the country, in answer to the growing needs of the local market. They have served and still been serving top firms in the service and construction industry, requiring them to be internationally competitive and up to world standards. To help the company meet these standards, the group generated some improvements on the existing quality system of the company. This was done by conducting a project study as an application of Statistical Quality Control. The length of the study includes documentation of the systems and procedures, manufacturing processes, product line, and the quality system of the company. In particular, the group chose to study uPVC Series 8 pipes produced in two machines: CM 65 and KMD 110 because of its high contribution on sales volume of the company. Through the use of tools such as the Streamline and Ishikawa Diagram, Check Sheet and Pareto Chart, the group has come up with three major problems encountered by the company. These are the occurrence of pipe defects such as uneven thickness, cracked bellhead and burned surface. It was determined that these problems were highly due to incorrect machine operational parameters, and lack of workers' dedication to quality control. These problems were further analyzed using control charts to determine if the process is in control. A variable control chart was done for the problem of uneven thickness and cracked bellhead. The control charts indicate points that are out of control and are due to assignable causes such as the use of a regrind material, machine downtime and change in the skill of the operator. These points were discarded and a new set of control limits was obtained until the process became in-control. A p chart was constructed for the problem of burned surface and results show that the process was out of control due to the use of regrind material. A new set of control limits was determined until the charts show that the process is in-control and the limits may be adopted for future production. Results of Process Capability Analysis indicate that the process of wall thickening for KMD 110 and Pipe molding for CM 65 are not capable and needs process improvement. Quality Cost Analysis further confirmed that the company incurs huge amount of costs in producing nonconforming pipes. To address the problems identified, the group suggested the following recommendations: introduction of a standard procedure for centering the bolts, use of statistical tools and implementation of a quality awareness program.